Phytochemical, Antioxidant, and Antibacterial Activities of Stem Bark Fractions of Eucalyptus globulus Against Multidrug-Resistant Bacterial Isolates - Abaka, AbdulAzeez Mumsiri; Dominic, Nazuwa; Emmanuel, Alex Yeri; Aliyu, Zayyad Dahiru (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The growing challenge of antimicrobial resistance (AMR) has intensified the need for alternative therapeutic agents, with medicinal plants offering promising solutions due to their bioactive compounds. This study investigated the antimicrobial and antioxidant properties of Eucalyptus globulus bark extracts against multidrug-resistant bacteria (Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus). Plant samples were collected from Adamawa State Polytechnic, Nigeria, authenticated (voucher ASP-765), and subjected to reflux extraction using hexane and water. Phytochemical analysis revealed alkaloids, phenols, tannins, glycosides, and terpenoids in both methanol and aqueous extracts, while flavonoids and steroids were absent in aqueous extracts, and methanol extracts lacked saponins. Antibacterial activity was assessed through agar well diffusion and broth dilution assays, demonstrating a concentration-dependent effect. Methanol extracts showed greater efficacy against E. coli and P. aeruginosa (12.8–13.8 mm inhibition zones), while aqueous extracts were most effective against S. aureus (19.3 mm at 100 mg/mL). Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values ranged from 25 to 50 mg/mL, with E. coli exhibiting the lowest MIC (25 mg/mL), highlighting the extract’s antimicrobial potential. The antioxidant activity was evaluated using phosphomolybdate and ferricyanide assays. The methanol extract exhibited strong free radical scavenging activity, with a total antioxidant capacity (TAC) expressed in ascorbic acid equivalents (AAE), although lower than pure ascorbic acid. Statistical validation (one-way ANOVA, p < 0.05) confirmed the significance of the results. These findings support the traditional medicinal use of E. globulus and its potential for combating antibiotic-resistant infections and oxidative stress-related conditions. Further studies are recommended to isolate bioactive compounds, determine mechanisms of action, and develop optimized therapeutic formulations for AMR management.